2018
DOI: 10.1038/s41598-018-21349-2
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex serologic platform for diagnosis of tick-borne diseases

Abstract: Tick-borne diseases are the most common vector-borne diseases in the United States, with serology being the primary method of diagnosis. We developed the first multiplex, array-based assay for serodiagnosis of tick-borne diseases called the TBD-Serochip. The TBD-Serochip was designed to discriminate antibody responses to 8 major tick-borne pathogens present in the United States, including Anaplasma phagocytophilum, Babesia microti, Borrelia burgdorferi, Borrelia miyamotoi, Ehrlichia chaffeensis, Rickettsia ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 63 publications
2
77
0
Order By: Relevance
“…In addition to B. miyamotoi peptides, we examined the reactivity to peptides from other tick-borne agents. In 2 samples, we detected IgG reactivity to specific epitopes of B. burgdorferi that were identified in our previous work (40). Subsequent examination of clinical history of these 2 individuals revealed that both had previously been diagnosed with Lyme disease.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…In addition to B. miyamotoi peptides, we examined the reactivity to peptides from other tick-borne agents. In 2 samples, we detected IgG reactivity to specific epitopes of B. burgdorferi that were identified in our previous work (40). Subsequent examination of clinical history of these 2 individuals revealed that both had previously been diagnosed with Lyme disease.…”
Section: Resultssupporting
confidence: 51%
“…The TBD-Serochip is a peptide array that consists of approximately 170,000 12-mer linear peptides designed from the protein sequence of the primary antigens of Anaplasma phagocytophilum , B. burgdorferi , B. miyamotoi , Babesia microti , Rickettsia rickettsii , Ehrlichia chaffeensis , Powassan virus and Heartland virus (40). The 12-mer peptides tile the sequence of each antigen with an 11 amino acid (aa) overlap to the preceding 12-mer peptide in a sliding window pattern.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptide microarray technology we use in this study allows for one serum sample to be assayed against six million unique 16-residue peptides, or for 12 samples to each be assayed against 392,000 peptides, on a single chip (Roche Sequencing Solutions, Madison, WI). The technology has been used in proteome-wide epitope mapping [30], profiling of antibody responses in autoimmune disease [31], profiling venom toxin epitopes [32], determining functions of cellular enzymes [33], de novo binding sequence discovery [34], epitope validation following phage display screening [35], and screening for tick-borne disease seroprevalence [36]. We previously used this tool to examine antibody responses in simian pegivirus (SPgV) and simian immunodeficiency virus (SIV) infections [37].…”
Section: Introductionmentioning
confidence: 99%